2021
DOI: 10.1371/journal.pntd.0009834
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of minimal hepatic encephalopathy by using an radiomics nomogram in chronic hepatic schistosomiasis patients

Abstract: Objective To construct an MR-radiomics nomogram to predict minimal hepatic encephalopathy (MHE) in patients with chronic hepatic schistosomiasis (CHS). Methods From July 2017 to July 2020, 236 CHS patients with non-HE (n = 140) and MHE (n = 96) were retrospective collected and randomly divided into training group and testing group. Radiomics features were extracted from substantia nigra-striatum system of a brain diffusion weighted images (DWI) and combined with clinical predictors to build a radiomics nomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As the mild form of hepatic encephalopathy, minimal hepatic encephalopathy is usually neglected clinically, and requires specific diagnostic methods. 11 Interestingly, our network showed that hepatic encephalopathy was closer to SIGs, whereas minimal hepatic encephalopathy was closer to SAMs. Our results suggested that hepatic encephalopathy might be a consequence triggered by complications derived from portal hypertension, but minimal hepatic encephalopathy might be a persistent, mild metabolic abnormality.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As the mild form of hepatic encephalopathy, minimal hepatic encephalopathy is usually neglected clinically, and requires specific diagnostic methods. 11 Interestingly, our network showed that hepatic encephalopathy was closer to SIGs, whereas minimal hepatic encephalopathy was closer to SAMs. Our results suggested that hepatic encephalopathy might be a consequence triggered by complications derived from portal hypertension, but minimal hepatic encephalopathy might be a persistent, mild metabolic abnormality.…”
Section: Discussionmentioning
confidence: 78%
“…4 Some common complications are not included in the existing classification, such as pulmonary hypertension, chronic kidney disease, minimal hepatic encephalopathy, and metabolic syndrome (including hypertension, diabetes, and hyperlipidemia). 10 , 11 Furthermore, the complications are usually co-occurring rather than presenting as isolated complications. 4 Thus, a more comprehensive classification is required to meet the clinical needs for therapy choice and prognosis prediction in advanced schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…The radiomics converts the medical images into highdimensional data by high-throughput extraction of quantitative features (Li et al, 2021). Nomogram is a diagnostic model that combines imaging and clinical information to determine an individualized prediction or treatment decision, and prognosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics can be used to extract many features from tomographic images via highthroughput computing and convert them into comprehensive quantified data (Gillies et al, 2016). DWI-based radiomics was considered a biomarker (Li et al, 2021). Combined analyses of the radiomics features and the clinical risk factors can produce a radiomics nomogram, which is becoming the most promising approach for individualized management (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation